Educação musical - uma nova abordagem (Centro Livre de Aprendizagem Musical - São Paulo - 1973 a 2001) - Suzigan, Maria Lúcia Cruz (2006)
This work intends to discuss the pedagogical project of CLAM - Free Center of Musical Learning, one of the first schools of music in the city of São Paulo to develop a different proposal of teaching-learning from the traditional schools. The focus is on the period from March 1973 to March 2001. It is an interdisciplinary work the first one concerning a brief history of Zimbo Trio and the CLAM. The second chapter analyses all the methodology developed in the school and examples of what repertoire was used. In the third chapter is about the creation and organization of the Department of Musical Education for Children, its methodology, repertoires, recitals and the use of this teaching-learning system for public and private schools, in particular Diadema - SP public school net.